Kewenangan Dan Pertanggungjawaban Notaris Dalam Pembuatan Perjanjian Pengikatan Jual Beli Tanah : Implikasi Terhadap Kepastian Hukum Dan Perlindungan Hukum Para Pihak) - Brigays, Chintia Ayala; Djaja, Benny; Sudirman, M. (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2025)
This study examines the authority and legal liability of Notaries in drafting the Sale and Purchase Binding Agreement (PPJB) for land and its implications for legal certainty and the protection of the parties involved. The main issue addressed is the inaccurate understanding of a Notary’s authority in practice (dassein), which is often equated with that of the Land Deed Official (PPAT), whereas normatively (dassolen) both have distinct boundaries as stipulated in the Law on Notary Positions and regulations on land rights transfer. The purpose of this research is to analyze the scope of a Notary’s authority, the forms of legal responsibility, and their contribution to ensuring legal certainty in land sale and purchase transactions. The research employs a normative juridical method with a statutory and conceptual approach through an examination of doctrines, legislation, and relevant court decisions. The results show that Notaries are authorized to prepare PPJBs as authentic deeds that provide perfect evidentiary value and secure the principal agreement between the seller and the buyer. However, the authority to transfer ownership rights remains with the PPAT through the Sale and Purchase Deed (AJB). A Notary’s legal liability covers civil, criminal, and administrative aspects, playing an essential role in preventive and repressive legal protection to ensure legal certainty in land transactions.